Berselawat Dengan Musik: Analisis Sama’ Al-Ghazali Dalam Majelis Hadrah Ishari - Danu Wibowo (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
The focus of the problem examined in this paper is to determine the relationship between music and the ISHARI hadrah assembly, where music can be used as a means of generating expression and strengthening the emotions of the congregation regarding their longing for the Prophet in the scope of research in the village of Sidosermo, Surabaya. This study used a descriptive qualitative approach, and to obtain data in this study, the authors used data collection techniques using observation, interview, and documentation methods. The theory used is to use the Sama’ analysis Imam al-Ghazali. He explained the theory, that there are three degrees when someone hears music (Sama'), including: Understanding, Feeling, and Expression. This research concludes that the function of music in ISHARI assemblies can be used as a means of generating expression. However, only a portion of the congregation could understand and feel the meaning of the ISHARI blessing. The things that can be felt include, (1) love or mahabbah, (2) longing or syawq, (3) feeling of melting or ecstasy.